Analysis of the Effect of Work Pressure and Work Stress on Job Satisfaction of PT. Avia Citra Dirgantara Abdul Rachman Saleh Airport Malang - Nadha Asmara Tri Kartika Sary; Andi Syaputra (CV. Rayyan Dwi Bharata, 2023)
Job satisfaction is an expression of employee satisfaction regarding how the work they do can benefit both themselves and the company. So every company is expected to pay attention to the level of job satisfaction experienced by its employees by paying attention to what factors can affect the level of job satisfaction. This study aims to determine how the effect of work pressure and work stress on job satisfaction of employees of PT. Avia Citra Dirgantara Abdul Rachman Saleh Airport Malang. This study uses a quantitative method with a research instrument using a questionnaire or questionnaire distributed to all employees of PT. Avia Citra Dirgantara Abdul Rachman Saleh Airport Malang. The data analysis used was multiple linear regression analysis, partial test (T-Test), simultaneous test (F-Test), and test of the coefficient of determination which was processed using SPSS for windows relase version 25. The results showed that there was a significant influence between work pressure on job satisfaction and there is no significant effect between work stress on job satisfaction of employees of PT. Avia Citra Dirgatara Abdul Rachman Saleh Airport Malang. This shows that the variables of work pressure and work stress are able to explain the job satisfaction variable of 26.7%, where the difference of 73.3% is explained by other variables not tested in this study.